Experimental analysis of Titanium Dioxide synthesis from synthetic rutile waste using a moderate acid concentration and temperature - Ahmad Mukifza Harun; Huzaikha Awang; Shahril Yusof; Eddy Mohd Farid Mohd Yusslee (2016)
The present study is to clarify the present influences of acid concentration and temperature of caustic hydrothermal method on extracting the titanium dioxide (TiO2) from synthetic rutile waste. In this experimental work, the caustic hydrothermal method comprises two processes: a decomposition and the sulphate process. The extracted titanium is characterized by using a electron dispersive X-ray spectroscopy to specify its chemical composition, field emission scanning electron microscope to determine the morphology and particle size, and lastly it is the X-ray diffraction to analyse the crystallinity of extracted titanium. In this study, we found that both acid concentration and temperature affected the TiO2 growth while the calcination process could improve the crystallinity of extracted titanium.